Labor reallocation in response to trade reform - Naércio Aquino Menezes Filho; Marc-Andreas Muendler (Center for Economic Studies and ifo Institute (CESifo), 2007)
Tracking individual workers across employers and industries after Brazil's trade liberalization in the 1990s shows that foreign import penetration and tariff reductions trigger worker displacements but that neither comparative-advantage industries nor exporters absorb displaced workers for years. There are significantly more displacements and fewer accessions in comparative-advantage industries and at exporters. These findings are robust to instrumenting trade barriers and export status with product demand at Brazil's export destinations and real exchange rate components. Worker effects are important predictors of labor turnover. Trade liberalization is associated with significantly more transitions to informal work status and self-employment. Output is reallocated to more productive firms but, given fast labor-productivity growth, this product reallocation is not accompanied by similar labor reallocation.
Keywords: F14; F16; J23; J63; 330; international trade; factor reallocation; labor demand and turnover; linked employer-employee data; Außenhandelsliberalisierung; Faktormobilität; Arbeitsnachfrage; Arbeitsmobilität; Dualökonomie; Außenhandelswirtschaft; Beschäftigungseffekt; Schätzung; Brasilien